Frequency and Outcome of Traumatic Subarachnoid Hemorrhage in patients presenting with Traumatic Brain Injury at Tertiary Care Hospital, Karachi - Rubab Qadir, Kinza Fatima, Rubiya Ali, Zulqarnain, Muhammad Muizzuddin, Muhammad Mohsin Jummani, Iram Bokhari, Mohammad Hasan (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the frequency and outcome of traumatic subarachnoid hemorrhage (tSAH) in patients presenting with traumatic brain injury. Method: A cross-sectional study was conducted at the Department of Neurosurgery, JPMC, Karachi from August 2021 to July 2022. Patients presenting with traumatic brain injury at the Department of Neurosurgery, JPMC, Karachi were enrolled in this study. A brief history of demographic information, duration, and mode of head injury was taken at the time of admission. CT scan brain was performed and interpreted.The findings of quantitative and qualitative variables (gender, smoking status, diabetes mellitus (DM) type II, hypertension, associated brain injuries, mode of head injury, tSAH, and good outcome) were recorded in the performance. Results: A total of 267 patients were enrolled in the study. The majority of the patients were aged between 21-48 years. Around 197(73.8%) patients were male and 75(28.1%) were female. The cause of traumatic brain injury was found to be road traffic accidents in 157(58.8%) individuals. The Glasgow coma scale (GCS) at presentation was 3-8 in (33.70%) of patients, 9 -13 in (43.07%) of patients, and 14-15 in (23.22%) of patients. At the time of discharge, GCS was 14-15 in (40.07%), 9-13 in (25.09%) patients, 3-8 in 23.59%, and 11.23% of patients died. It was found that both age (p=0.003), gender (p=0.002), and other brain injuries (p=0.0001) were significantly associated with the outcome. Conclusion: The present study revealed the outcome of traumatic subarachnoid hemorrhage (tSAH) in the majority of the patients was unfavorable. Age, diabetes mellitus, smoking, and other associated brain injuries were significantly related to unfavorable outcomes in the study. Keywords: Traumatic subarachnoid hemorrhage, traumatic brain injury, GCS, neurosurgery